2019
DOI: 10.1016/j.brs.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of peripheral auditory pathway activation does not affect motor responses from ultrasound neuromodulation

Abstract: Background: Recent studies in a variety of animal models including rodents, monkeys, and humans suggest that transcranial focused ultrasound (tFUS) has considerable promise for noninvasively modulating neural activity with the ability to target deep brain structures. However, concerns have been raised that motor responses evoked by tFUS may be due to indirect activation of the auditory pathway rather than direct activation of motor circuits. Objective: In this study, we sought to examine the involvement of per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 38 publications
(38 reference statements)
5
90
1
Order By: Relevance
“…We hypothesize that Sato et al observed a combined effect of direct USN and auditory effects but the direct effects were below the detection threshold of the in vivo optical system, which would primarily be sensitive to cortical activation in the living animal. This interpretation is consistent with in vivo studies in genetically deafened mice that demonstrate motor responses from transcranial ultrasound 42 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We hypothesize that Sato et al observed a combined effect of direct USN and auditory effects but the direct effects were below the detection threshold of the in vivo optical system, which would primarily be sensitive to cortical activation in the living animal. This interpretation is consistent with in vivo studies in genetically deafened mice that demonstrate motor responses from transcranial ultrasound 42 .…”
Section: Discussionsupporting
confidence: 89%
“…This metric only included the 24 s following the onset of ultrasound in pulsed trials to keep the total amount of pressure cycles delivered comparable (250 kilocycles in continuous wave trials, 240 kilocycles in pulsed trials). The response rate is much lower than what is reported in in vivo murine models where motor responses > 80% were found for very similar US parameters (500 kHz 80 ms pulses at 300 kPa or 2.9 W/cm 2 I SPTA ) 42 . Factors inherent to our experimental design may have contributed to these low response rates.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…With these latest developments, rTUS appears to be very promising and offers a novel and competitive neurostimulation technique. When compared to rTMS, rTUS offers a higher spatial resolution ( Pinton et al, 2012 ), a larger targeting envelope ( Krishna et al, 2018 ) and the absence of noise or mechanical vibration during stimulation ( Mohammadjavadi et al, 2019 ). This technique shows promise in the non-invasive exploration of cognition with non-human primate models.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Recent animal data have shown that these can be independently modulated by transcranial ultrasound and modulations cannot be explained by pure acoustic stimulation effects. [37,38] Ultrasound brain stimulation is typically performed with single channel systems equipped with neuronavigation for individualized targeting of the patient's brain. The novel technique has two major advantages compared to existing electromagnetic brain stimulation methods, for which several clinical trials exist [39] : 1) unprecedented precision for brain area targeting (independent of patho-logical conductivity changes) and 2) access to deep brain areas, which has not been possible previously.…”
Section: Brain Stimulation Therapymentioning
confidence: 99%